SARS-CoV-2 Molecular Epidemiology Can Be Enhanced by Occupational Health: The Experience of Monitoring Variants of Concern in Workplaces in Rio de Janeiro, Brazil - Kuriyama, Sergio N.; Farjun, Bruna; Henriques-Santos, Bianca Monteiro; Cabanelas, Adriana; Abrantes, Juliana Lourenço; Gesto, João; Fidalgo-Neto, Antonio A.; Souza, Thiago Moreno L. (Frontiers in Medicine, 2022)
The emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to extra caution in workplaces to avoid the coronavirus disease 2019 (COVID-19). In the occupational environment, SARS-CoV-2 testing is a powerful approach in providing valuable information to detect, monitor, and mitigate the spread of the virus and preserve productivity. Here a centralized Occupational Health Center provided molecular diagnosis and genomic sequences for companies and industries in Rio de Janeiro, Brazil. From May to August 2021, around 20% of the SARS-CoV-2 positive nasopharyngeal swabs from routinely tested workers were sequenced and reproduced the replacement of Gamma with Delta variant observed in regular surveillance programs. Moreover, as a proof-of-concept on the sensibility of the occupational health genomic surveillance program described here, it was also found: i) the primo-identification of B.1.139 and A.2.5 viral genomes in Brazil and ii) an improved dating of Delta VoC evolution, by identifying earlier cases associated with AY-related genomes. We interpret that SARS-CoV-2 molecular testing of workers, independent of symptom presentation, provides an earlier opportunity to identify variants. Thus, considering the continuous monitoring of SARS-CoV-2 in workplaces, positive samples from occupation health programs should be regarded as essential to improve the knowledge on virus genetic diversity and VoC emergence.